Conversion surgery for metastatic gastric cancer at 2 years after initial diagnosis of cancer of unknown primary with metastasis of cervical lymph nodes and ovary: a case report - Masaki Suzuki; Hisashi Hosaka; Yasuyuki Fukai; Yasushi Mochida; Daigo Ozawa; Norimichi Kogure; Kazunosuke Yamada; Hitoshi Ojima (Surgical Case Reports)
Abstract Background Patients with stage IV gastric cancer have a poor prognosis despite improvements in intensive treatment regimens, including chemotherapy. Recently, conversion surgery has received much attention as it can provide long-term survival in stage IV gastric cancer patients who are responsive to chemotherapy. Herein, we describe the case of a patient who underwent conversion surgery for metastatic gastric cancer that was performed over 2 years after an initial diagnosis of cancer of unknown primary (CUP) with metastasis of the cervical lymph nodes and the ovary. Case presentation A 67-year-old woman with cervical lymphadenopathy was referred to our hospital. Computed tomography showed left cervical lymphadenopathy and bilateral ovarian enlargement. Endoscopic survey revealed no signs of malignancy in the upper or the lower gastrointestinal tract. Pathological findings after cervical lymphadenectomy revealed a signet-ring cell carcinoma and were suggestive of gastric cancer metastases. However, multiple evaluations yielded no evidence of gastric cancer and the patient was diagnosed with CUP. She was prescribed chemotherapy for gastric cancer and underwent bilateral oophorectomy after undergoing chemotherapy for 18 months. Pathologic analysis of oophorectomy tissue revealed findings identical to those seen in the cervical lymph nodes. At about 2 years after the initial diagnosis, an esophagogastroduodenoscopy revealed evidence of gastric cancer. We performed a distal gastrectomy with D2 lymphadenectomy. Her postoperative course was uneventful and she remains alive with no signs of disease recurrence at 3 months post-surgery. Conclusions To the best of our knowledge, this is the first report describing successful conversion surgery for stage IV gastric cancer in a patient whose cancer was definitively diagnosed 2 years after an initial diagnosis of CUP.